Coastal Erosion Prevention with Nature-Inspired Geotechnics - Dubey, Anant (2024)
Around 80% of Australian residents live near its beautiful coastline. Unfortunately, coastal land and infrastructure are at a greater risk than ever due to the unprecedented increase in coastal erosion rates driven by the climate change-induced rise in the mean sea level (MSL). Traditional erosion control measures, such as mechanical compaction, cement-based structures, synthetic binders, and soil replenishment, struggle to meet modern sustainability demands. In contrast, natural beach rocks exhibit remarkable resistance to erosion, formed through complex processes involving nearshore microbial life. The nearshore microbial life produces macromolecules of the polymeric substances that capture the metals and precipitate stable crystal units upon the availability of nutrients under specific conditions, forming erosion-resistant beach rocks. Such beach rocks in nature take years to decades to form through numerous complex geochemical pathways. It is not only critical to unpin these geochemical reactions but also to engineer them to expedite the rates of formation.